Nilai Religius pada Novel Bulan Jatuh di Pangkuanku Karya Muhammad Suwardi: Kajian Struktural Dinamik - Yeyet Kusmayati (UHAMKA Graduate School Thesis Abstract Collection, 2016)
purposed to describe novel intrinsic element, religious values in Bulan Jatuh di Pangkuanku novel by Muhammad Suwardi and implication on literature appreciation learning. The method of this research was content analysis with qualitative descriptive approaching and the dynamic structural study. Qualitative descriptive approach was purposed to reveal the real fact, situation, and phenomenon. This analysis method is a technique was used to analyze and comprehend the text, explain as objective as from the content the novel used. The result showed that Bulan Jatuh di Pangkuanku novel by Muhammad Suwardi, based on areview of the religious value in Islam, can be grouped into four categories, they are: first, relationship between Allah and humans. It has seen that the humans must believe to Allah SWT, grateful of healthy, and Allah’s mercy. We must be honest in rightness, in every situation we must pray to Allah and accept Allah’s life fate. Second, relationship human and the others with religious value is we must appreciate, help each others, do honestly and appreciate the husband. Third, relationship human themselves, can be realized in preventing hopeless, arrogant, and greedy. We must be patient in facing the life. Fourth, relationship humans and the environment that let’s preserve the nature and animal as their habitat. In this research hopefully the readers, students and teachers could appreciate popular novel as a learning material and giving motivation in applying positive life value, particularly religious.